Impact on air quality of cruise ship emissions in Naples, Italy. (August 2018) - Murena, F.; Mocerino, L.; Quaranta, F.; Toscano, D.
Abstract: The Municipality of Naples, with about 1 million residents and about 3 million people living in the surroundings, suffers, as for many a city, from low air quality, as demonstrated by the concentration level of pollutants measured by fixed monitoring stations of the Regional Air Quality Network. The port of Naples is among the most important ports in the Mediterranean sea with a large traffic of passengers and goods. Therefore, it contributes to atmospheric pollution of the nearby urban area with ship emissions. Public authorities need to know the contribution of different sources of atmospheric pollutants to put effective environmental policies into practice. In this article, a bottom-up methodology has been developed to assess the amount of atmospheric pollutants emitted by cruise ships traffic and its impact on the atmospheric pollution in Naples. A detailed description of in-port activities of cruise ships has been applied to calculate emission rates of NOx and SOx by using standard procedures corrected and integrated by real data to better evaluate actual engine power applied and fuel consumption. Considered activities include: navigation in port both at arrival and departure; maneuvering for berthing and unmooring and hoteling at berth. The study covers all cruise ship calls during the year 2016. The impact of cruise ship emissions on the urban area has been assessed by using the Gaussian puff model CALPUFF, thus obtaining contour maps of 1-h and year average values. Finally, in order to assess the contribution of cruise ship emissions to air quality, simulations have been compared with concentrations measured at fixed monitoring stations and during a monitoring campaign. Graphical abstract: Image 1 Highlights: Accurate evaluation of NOx and SOx cruise ship emissions in Naples. Cruise ship emissions represent an important fraction of overall ship emissions in Naples. The impact of cruise ship emissions can be relevant for short time averaged concentration levels. The impact of cruise ship emissions is not negligible on long time averaged concentration levels.